A Concept Model of Mining Monotowns Sustainable Development; E3S Web of Conferences; Vol. 41 : International Innovative Mining Symposium - Artyukhova N. A. Nataljya Aleksandrovna; Roshchina I. V. Irina Viktorovna; Kalyanova G. S. Galina Sergeevna; Kaz M. S. Mikhail Semenovich (2018, 2018)
Title screen